2022
DOI: 10.1002/jocb.532
|View full text |Cite
|
Sign up to set email alerts
|

Is Shared Leadership Really as Perfect as We Thought? Positive and Negative Outcomes of Shared Leadership on Employee Creativity

Abstract: The link between shared leadership and employee creativity has been consistently labeled as positive in prior studies, discounting a possible negative relationship. A parallel mediation model was constructed to establish the favorable and unfavorable outcomes of shared leadership on employee creativity. The model is based on the job demands–resources model that originates from conservation of resource theory. Psychological safety and role stress play positive and negative mediating roles, respectively. The the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 118 publications
0
13
0
Order By: Relevance
“…Leadership has gained traction these days as a factor influencing project outcomes (Lorinkova & Bartol, 2021;Imam & Zaheer, 2021;Imam, 2021). Scholars (e.g., Klasmeie & Rowold, 2022;Wang & Peng, 2022) have highlighted the value of shared leadership as an effective leadership style. We tested a comprehensive model of shared leadership with project success including internal marketing, internal communication and thriving as mediators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leadership has gained traction these days as a factor influencing project outcomes (Lorinkova & Bartol, 2021;Imam & Zaheer, 2021;Imam, 2021). Scholars (e.g., Klasmeie & Rowold, 2022;Wang & Peng, 2022) have highlighted the value of shared leadership as an effective leadership style. We tested a comprehensive model of shared leadership with project success including internal marketing, internal communication and thriving as mediators.…”
Section: Discussionmentioning
confidence: 99%
“…It is argued that project success depends on an appropriate leadership style (Castellano, 2021;Jiang, 2014;Lee, 2021). In an assessment of the current studies on the effect of leadership on project outcomes (Ali, 2021;Bartol & Lorinkova, 2021;Imam & Zaheer, 2021;Imam, 2021;Lorinkova, 2021), several scholars (for example, Klasmeie & Rowold, 2022;Peng & Wang, 2022) have stressed the usefulness of shared leadership. Shared leadership denotes leadership whereby responsibilities and leadership roles are shared between team members (Conger & Pearce, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…D 'Innocenzo et al, 2016;Lorinkova and Bartol, 2021;Wang et al, 2017). But at the same time, they also bring about a series of negative impacts, such as power struggle (Ji, 2018), role stress (Wang and Peng, 2022) and low decision-making efficiency (Zhu et al, 2018), which will be discussed in detail below.…”
Section: Definition and Characteristics Of Shared Leadershipmentioning
confidence: 99%
“…Role overload is a kind of role stress caused by the lack of necessary skills or time to realize the role expectation when an individual is faced with multiple roles. It is proposed that employees under shared leadership conditions need to assume the responsibilities of both leader and follower, and are placed under more role expectations, which will bring greater work pressure to them and lead to the perception of high role load (Wang and Peng, 2022). In addition, the empirical study by Evans et al (2021) indicated that when peer engagement was low and employees needed to take interpersonal responsibilities, shared leadership will damage individual enjoyment and performance due to role stress (i.e.…”
Section: Role Stressmentioning
confidence: 99%
“…Extant research on improvisation mainly focused on the effect of the team situation and individual traits in shaping individual and team improvisation [ 12 , 13 , 14 ], while less emphasis is placed on leadership, which plays a pivotal role in creating conditions that enable teams to be effective [ 1 , 9 , 15 ]. Moreover, the practice of informal leadership has become more widespread in current organizations as the emphasis on teammate cooperation and coordination is increasing [ 16 , 17 ]. Organizational scholars have argued that flexible team interaction patterns promote efficient team responses to unexpected situations [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%